The role of the school in developing the moral values of students from the teachers perspective of the Kasbah Al-Mafraq schools - Al-badi, Rogayah Awwad (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to The role of the school in developing the moral values of students from the teachers perspective of the Kasbah Al-Mafraq schools, To achieve this study, the descriptive approach was used, where a questionnaire was developed, consisting of three areas(School administration, educational guide, activities and celebrations) with (23) paragraphs, and its validity and stability was verified, and then it was distributed on the sample of the study which was consisted of (150) teachers in the schools of Kasabat Al Mafraq. The result of the study showed that the role of the school in developing the moral values of students from the teachers perspective of the Kasbah Al-Mafraq schools was middle and with an average arithmetic (3.01). The results also showed no significant differences in the evaluations of the study’s sample members for the role of the school in developing the moral values of students from the teachers perspective of the Kasbah Al-Mafraq schools according to the gender variable, On the two levels (school administration and educational counselor) and at the total level. In the light of the results, the study recommended that the school administration should provide a safe, violence-free school environment for students, and that the curricula be updated and developed periodically to enhance students’ values and good moral behavior.